2018
DOI: 10.1159/000492126
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction Seems to Trigger Depression in Female Multiple Sclerosis Patients

Abstract: Background: In women with multiple sclerosis (MS), depression and sexual dysfunction (SD) are common. Whether SD promotes depression or vice versa remains unclear despite therapeutic relevance. Therefore, we aimed to assess whether SD more likely triggers depression or vice versa. Methods: In 83 female MS patients and 21 age-matched healthy women, we assessed depression, using the Beck Depression Inventory-V (BDI-V), and SD using the Female Sexual Function Index (FSFI). We diagnosed depression with BDI-V-score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
(80 reference statements)
1
16
0
Order By: Relevance
“…Different patient characteristics were found to be associated with SD including advancing age, lower educational level, and poor QoL . MS‐related parameters found to be associated with SD were longer disease duration, progressive MS, greater neurological disability, worse physical functions, fatigue, urinary problem, and poor cognitive function .…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Different patient characteristics were found to be associated with SD including advancing age, lower educational level, and poor QoL . MS‐related parameters found to be associated with SD were longer disease duration, progressive MS, greater neurological disability, worse physical functions, fatigue, urinary problem, and poor cognitive function .…”
Section: Discussionmentioning
confidence: 98%
“…Case‐control studies demonstrated that SD was more commonly reported in MS compared to healthy controls . There were 14 case‐control studies exploring SD in PwMS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations